1996
DOI: 10.1037/0033-2909.120.2.189
|View full text |Cite
|
Sign up to set email alerts
|

An integrative framework for explaining reactions to decisions: Interactive effects of outcomes and procedures.

Abstract: The authors suggest that procedural and distributive factors interactively combine to influence individuals' reactions to their encounters with other people, groups, and organizations. Results from 45 independent samples (reviewed herein) show that (a) level of procedural justice is more positively related to individuals' reactions when outcome fairness or valence is relatively low and (b) level of outcome fairness or valence is more positively related to individuals' reactions when procedural justice is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

73
911
11
37

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,046 publications
(1,046 citation statements)
references
References 78 publications
73
911
11
37
Order By: Relevance
“…Numerous studies (for an overview, see Brockner & Wiesenfeld, 1996) have demonstrated that reactions to unfavourably unfair outcomes are generally more negative following unfair procedures rather than fair procedures. Based on these findings, it could be argued that outgroup authorities procedures should have a stronger impact when social comparison information indicates an unfavourably unfair rather than a fair outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies (for an overview, see Brockner & Wiesenfeld, 1996) have demonstrated that reactions to unfavourably unfair outcomes are generally more negative following unfair procedures rather than fair procedures. Based on these findings, it could be argued that outgroup authorities procedures should have a stronger impact when social comparison information indicates an unfavourably unfair rather than a fair outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The job-strain model was developed in the context of industrialization in parallel to a widely applied work-motivation theory with some core aspects of work that are close to the job-control concept (ie, task variety, and autonomy) (59,60). The ERI model shares elements with the distributive justice model, another work motivation theory (10), and taps features of postmodern flexible worklife, such as temporary employment and job insecurity (61). The most recent developments in work motivation theories involve procedural and relational justice at work (11,13), which has been shown to be an important moderator of employee responses (62)(63)(64)(65).…”
Section: Directions Of Future Researchmentioning
confidence: 99%
“…While effort-reward imbalance defines disproportionate costs for an employee in terms of gains received (ie, a distributive injustice condition) the latest research on work stress has also focused on the two remaining aspects of justice (8)(9)(10). Procedural justice indicates whether decision-making procedures include input from affected parties, are consistently applied, suppress bias, are accurate, are correctable, and are ethical (11).…”
mentioning
confidence: 99%
“…Of key importance, the implementation plan also must consider the common barriers to change within an organization and intentionally address them. Some effective change strategies that should be consciously considered include (Brockner & Wiesenfeld, 1996): Organization. In particular, the apparent widespread accountability uncertainty for managing risks and information gaps in planning and decision making.…”
Section: Model Component 4 Implementationmentioning
confidence: 99%